The Implementation of Drilling Technique for Improving Pronunciation of Culinary Students - Daniel Lucky; Fajaryani, Nunung; Handayani, Reli (Langue (Journal of Language and Education), 2025)
Nowadays, the use of the drilling technique integrated with native speaker audio as a teaching aid is considered effective in overcoming pronunciation problems. This research investigates the implementation of the drilling technique to improve the pronunciation of culinary students at a vocational high school in Jambi. A Classroom Action Research (CAR) method was used, involving 33 students from the XI Culinary II class at SMKN 6 Kota Jambi. The research was carried out in two cycles, incorporating pre-tests, post-tests, observations, and interviews. The findings show significant improvement in the students’ pronunciation and engagement after the application of the drilling technique. The study concludes that drilling can be a highly effective method for enhancing students’ pronunciation skills in English language learning.